2017
DOI: 10.1021/acs.jpcc.7b01573
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Difference in Photophysical Properties of Cyclometalated Iridium(III) and Rhodium(III) Complexes by Detailed Time-Dependent Density Functional Theory and Frontier Molecular Orbital Supports

Abstract: Two sets of new mononuclear cyclometalated complexes of the types [MIII(ppy)2(L)] (Ir1 and Rh1) and [MIII(bzq)2(L)] (Ir2 and Rh2) [where M = Rh/Ir; L = N-(furan-2-ylmethyl)-2-pyridinecarboxamide; ppy = 2-phenylpyridine (1); bzq = benzo­[h]­quinoline (2)] are presented to understand the significant differences of emission behaviors between Ir­(III) and Rh­(III) complexes. The complexes were fully characterized by using physicochemical and spectroscopic tools along with the detailed structural studies of Ir1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 79 publications
5
33
0
Order By: Relevance
“…At this point, it is important to note that the non‐radiative T 1 → 3 MC→S 0 process must overcome two energy barriers, this is for the T 1 → 3 MC and 3 MC→S 0 pathways. Theoretical studies have shown that the T 1 → 3 MC barrier is ∼0.4 eV when the 3 MC state lies below the T 1 state [ E ( 3 MC)< E (T 1 )]; while, the barrier is higher in ∼1.0 eV when E ( 3 MC)> E (T 1 ). In all the cases, the barrier for the 3 MC→S 0 process is at least 80% lower than the T 1 → 3 MC path; thus, the T 1 → 3 MC process is the limiting step in the non‐radiative pathway .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At this point, it is important to note that the non‐radiative T 1 → 3 MC→S 0 process must overcome two energy barriers, this is for the T 1 → 3 MC and 3 MC→S 0 pathways. Theoretical studies have shown that the T 1 → 3 MC barrier is ∼0.4 eV when the 3 MC state lies below the T 1 state [ E ( 3 MC)< E (T 1 )]; while, the barrier is higher in ∼1.0 eV when E ( 3 MC)> E (T 1 ). In all the cases, the barrier for the 3 MC→S 0 process is at least 80% lower than the T 1 → 3 MC path; thus, the T 1 → 3 MC process is the limiting step in the non‐radiative pathway .…”
Section: Resultsmentioning
confidence: 99%
“…Theoretical studies have shown that the T 1 → 3 MC barrier is ∼0.4 eV when the 3 MC state lies below the T 1 state [ E ( 3 MC)< E (T 1 )]; while, the barrier is higher in ∼1.0 eV when E ( 3 MC)> E (T 1 ). In all the cases, the barrier for the 3 MC→S 0 process is at least 80% lower than the T 1 → 3 MC path; thus, the T 1 → 3 MC process is the limiting step in the non‐radiative pathway . In this framework, the access to the 3 MC states can be avoided by the adequate assembly of the emitting device in a solid host, avoiding (or decreasing) the intramolecular motions associated with the stretching Ir‐ligand vibrations; hence, increasing the energy barriers of the limiting T 1 → 3 MC step.…”
Section: Resultsmentioning
confidence: 99%
“…In order to obtain correct molecular constructions, the implicit solvation model based on density (SMD) is considered with density functional theory (DFT) and its time-dependent (TD) method. The TD-DFT functional method has been confirmed by contemporary researchers to be efficient and accurate for investigating photochemical reactions. The dielectric constant (ε) has been set as 38.8 to simulate the acetonitrile solution environment in experiment. All geometric constructions are fully optimized by Gaussian 09 software carried out at B3LYP-D3/6-31G­(d,p) calculation level, the transition-state constructions are calculated by the Berny arithmetic method .…”
Section: Computational Methodsmentioning
confidence: 99%
“…While the photophysical properties of the Ir III compounds are superior to those of the corresponding Rh III complexes, and therefore make the iridium complexes more useful with regard to diagnostic and phototherapeutic studies, this is not the general case for the antiproliferative properties. For example, while the iridium complex [Ir(ptpy) 2 (4,4'‐dinonyl‐2,2'‐bipy)] + (ptpy = para ‐tolyl‐pyridinato) was much more effective towards transfected HEK293T cells than its rhodium congener, the rhodium complexes [Rh(phquin) 2 (4,4'‐R 2 ‐2,2'‐bipy)] + (phquin = phenylquinolinato) performed much better in MDA‐MB‐231 cells (R 2 = diphenyl) or RAW264.7 cells (R 2 = dinonyl) than their iridium counterparts.,, Besides the nature of the metal, the substituents on the cyclometallating ligands as well as on the ancillary ligand have a great influence on the cancerostatic performance of these complexes.…”
Section: Introductionmentioning
confidence: 99%
“…[3] It was also shown that modifications of the cyclometallating ligand "C ∧ N" and/or the ancillary ligand "N ∧ N" allowed both fine-tuning of the anticancer and imaging properties. [4] While the photophysical properties of the Ir III compounds are superior to those of the corresponding Rh III complexes, [5] and therefore make the iridium complexes more useful with regard to diagnostic and phototherapeutic studies, this is not the general case for the antiproliferative properties. For example, while the iridium complex [Ir(ptpy) 2 (4,4Ј-dinonyl-2,2Јbipy)] + (ptpy = para-tolyl-pyridinato) was much more effec-structures of compounds 1b and 4a in the solid state were determined by single-crystal X-ray diffraction.…”
Section: Introductionmentioning
confidence: 99%